Die belewenis van die pasiënt en die verpleegkundige tydens tuberkulose-onderrig - M Strydom; M Greeff; A Nel (AOSIS, 2000)
This article focused on the problem that patients suffering from tuberculosis often stop taking their prescribed medicine and become defaulters. Although various factors could possibly contribute to the non compliance of the patients, this research had focused only on the teaching-learning situation. The experience of both the primary health nurse and the patient suffering from tuberculosis, during the teaching-learning situation in tuberculosis education, has been explored and described within the context of the North West Province. Phenomenological interviews were conducted with primary health nurses and defaulting patients suffering from tuberculosis. Interviews were recorded on tape and transcribed verbatim. The method of content analysis was used. The research has proven that adult-teaching principles have not been established in the teaching-learning situation and that the parent-child ego state predominates in communication.